Smart Detection System (Alcohol) - MASRI, MASZRIN; AZLINA BINTI BAHARI (Progress in Engineering Application and Technology, 2021)
The key idea to propose this system is to provide road protection for drunk drivers. By providing road protection from drunk driving, a smart detection system is designed to detect alcohol using the MQ3 sensor. As the device senses alcohol in human breath, the dc motor that indicates the ignition of the car is turned off and the buzzer is triggered to warn the surroundings that the driver is not able to drive the car with caution. In addition, when the BAC level is above the threshold, the position of the drunk driver will be transmitted to our mobile using the Blynk application. This machine can be evidence of performance by solving any constraint, as the internet connectivity of the wifi module can be enhanced